When High Spending Meets Low Walkability: The Accessibility Paradox in a Living Heritage Urban District - Anak Agung Ayu Gita Kusuma Astuti; I Gusti Ngurah Oka Widjaya; Ni Kadek Sri Mirayani; Ni Putu Ariningsih; Ni Wayan Gita Sadhana Savitri (Yayasan Ghalih Pelopor Pendidikan, 2026)
This study examines the structural paradox between high tourist expenditure concentration and infrastructural accessibility constraints in the Gajah Mada Heritage Area, Denpasar. Drawing on secondary data from the 2025 Denpasar Tourist Expenditure Survey, the study analyses micro spending patterns, attraction preferences, and satisfaction with traffic conditions using descriptive and gap analysis approaches. Results reveal that retail spending accounts for 20 percent of average daily domestic tourist expenditure, with visitation to shopping zones exceeding 80 percent, confirming the area’s function as a cultural shopping district. However, 49 percent of domestic visitors report dissatisfaction with traffic congestion, indicating a critical accessibility deficit. Tourist interest in living heritage attractions significantly exceeds that of static historical sites, suggesting a shift toward performative authenticity. The findings demonstrate that spatial constraints generate implicit economic costs by limiting dwell time and consumption opportunities. Revitalization strategies must therefore prioritize walkability oriented planning to sustain economic vitality in urban heritage corridors.